IPF, comorbidities and management implications: Patient case 2 - Hilberg, Ole (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Patient presentation and diagnosis The patient is a 50-year-old woman who was referred to a tertiary centre with an HRCT showing definite UIP and a 6-minute walking distance of 145 metres. She was severely ill at presentation with a diffusion capacity of just 20%. The patient had a history of peripheral arterial disease and had undergone both aortofemoral and femoro-femoral bypass due to arteriosclerosis and gluteal ischaemia. She also was suffering from renal impairment and had recently quit smoking. [...]